2010
DOI: 10.1111/j.1538-4616.2010.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Monetary Policy in a Model with Agency Costs

Abstract: This paper integrates a fully explicit model of agency costs into an otherwise standard Dynamic New Keynesian (DNK) model in a particularly transparent way. A principle result is the characterization of agency costs as endogenous mark-up shocks in an output-gap version of the Phillips curve. The model's utility-based welfare criterion is derived explicitly and includes a measure of credit market tightness which we interpret as a risk premium. The paper also fully characterizes optimal monetary policy and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 23 publications
5
117
0
Order By: Relevance
“…Weaknesses in macroprudential policies mean monetary policy more likely needs to respond to financial conditions. Indeed, in models where macroprudential policy is absent or time invariant, but with financial "distortions" still present, optimal monetary policy responds to some degree to financial conditions, in addition to output and inflation (Curdia and Woodford, 2009, Carlstrom and Fuerst, 2010, Adam and Woodford, 2013.…”
Section: A Macroprudential and Monetary Policiesmentioning
confidence: 99%
“…Weaknesses in macroprudential policies mean monetary policy more likely needs to respond to financial conditions. Indeed, in models where macroprudential policy is absent or time invariant, but with financial "distortions" still present, optimal monetary policy responds to some degree to financial conditions, in addition to output and inflation (Curdia and Woodford, 2009, Carlstrom and Fuerst, 2010, Adam and Woodford, 2013.…”
Section: A Macroprudential and Monetary Policiesmentioning
confidence: 99%
“…Examples of this line of research can be found in Kiyotaki and Moore (1997), Carlstrom, Fuerst, and Paustian (2010), and Gertler and Kiyotaki (2010). Credit constraints arise because lenders cannot force borrowers to repay their debts unless the debts are secured by some form of collateral.…”
Section: A Selected Review Of the Literaturementioning
confidence: 99%
“…Over the past two decades, there have been important advances in the theoretical literature on the macroeconomic impact of financial frictions. Notable contributions to the literature include Kiyotaki and Moore (1997), Bernanke, Gertler, and Gilchrist (1999), Christiano, Ilut, Motto, and Rostagno (2010), Carlstrom, Fuerst, and Paustian (2010), Curdia and Woodford (2010) and Gertler and Kiyotaki (2010). This research shows that credit market frictions (due to information asymmetry, agency costs or collateral constraints) act as a financial accelerator that in turn leads to an amplification of business cycles, and highlights the mechanisms through which credit market conditions are likely to impact the real economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Collaterals rise at high level of economic activity, making credit available and cheap, and the reverse happens at low level of economic activity. The debt to asset value ratio is predicted to fall in the 1 Theoretical literature has studied the amplifying eect of shocks near the steady state, for example, see Carlstrom, Fuerst (2009), and Curdia and Woodford (2009a,b). boom and rise in recessions.…”
Section: Introductionmentioning
confidence: 99%